(untitled) (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2026)
This study aims to examine the effect of motivation on employee performance through job satisfaction as a mediating variable among civil servants at dr. H. Moch. Ansari Saleh Regional General Hospital. A quantitative approach with an explanatory research design was employed in this study. The population consisted of 777 civil servants, comprising both permanent civil servants (Pegawai Negeri Sipil-PNS) and government employees with work agreements (Pegawai Pemerintah dengan Perjanjian Kerja-PPPK). A total of 264 respondents were selected using a proportional random sampling technique. Data were collected through questionnaires and analysed using the Partial Least Squares Structural Equation Modelling (PLS-SEM) method with SmartPLS software. The findings reveal that motivation has a positive and significant effect on job satisfaction. Job satisfaction also has a positive and significant effect on employee performance. However, motivation does not have a significant direct effect on employee performance. Furthermore, the mediation analysis demonstrates that job satisfaction significantly mediates the relationship between motivation and employee performance. These findings indicate that enhancing employee motivation alone is insufficient to directly improve performance unless it is accompanied by increased job satisfaction. Therefore, job satisfaction serves as a crucial mechanism linking motivation to employee performance. This study contributes to the human resource management literature in the healthcare sector by providing empirical evidence regarding the mediating role of job satisfaction in the relationship between motivation and employee performance among public hospital employees. Keywords: motivation; job satisfaction; employee performance; public hospital; PLS-SEM